INTERACTION OF ELEMENTAL GOLD SURFACE WITH FLUIDS: A KEY TO UNDERSTANDING MECHANISMS OF RECONDENSATION AND MOBILIZATION OF GOLD UNDER ENDOGENIC AND EXOGENIC CONDITIONS - Shchegol'kov Yu.V.; Tauson V.L.; Lipko S.V.; Medvedev V.Ya.; Pochekunina M.V.; Ivanova L.A. (My University, 2007)
The inoxidizability of pure metallic gold and its stability under the influence of strong dry oxidants like oxygen, chlorine, and sulfur are universally recognized. The resistance to corrosion is a characteristic feature of noble metals (NM), particularly platinum and gold. Therefore, these metals are used as jewellery materials, elements of electronic chips, and inoxidizable mats for growing crystals and films (e.g., in production of crystalline silicon in platinum crucibles). However, all these properties are related to massive NM. The situation changes drastically in the case of nano-scale particles and surface layers. Experiments with impulse radiolysis showed that the redox potential of gold atoms in water is close to –1.5 V. Therefore, gold is a strong reductant; i.e., isolated “gold atoms would be instantly oxidized in the air!”. In other words, if we could isolate a monolayer of gold atoms, it would be oxidized in the air. At the surface, atoms only partially belong to the solid body. Therefore, oxidation starting with the adsorption of an oxidant should always be present to a certain extent.